Performance of hybrid reinforced metal matrix composite brake disc: simulation approach - Fatchurrohman, Nanang; W. K., Gan (Trans Tech Publications Ltd, 2021)
A brake disc plays an important role in the vehicle and it is used to stop or decrease the velocity of the vehicle. The demand of metal matrix composites (MMCs) is greatly increased in fabricating the brake disc since it having a low density and high thermal conductivity. Over-heating will lead to the malfunction of the braking system and affect the safety of vehicle. Low weight of brake disc can decrease the use of fuel of the vehicle thus improve the fuel usage efficiency. This paper focussed to determine the suitability of AlSiCGr hybrid MMCs compared to cast iron in terms of thermal and structural properties for brake disc. Both design of brake disc were proposed and modelled using CATIA and then imported to ANSYS software for structural and thermal analysis. The simulation results showed that AlSiCGr hybrid MMCs brake disc has higher thermal and structural performance compared to the original cast iron brake disc.